2006
DOI: 10.1152/ajpgi.00289.2005
|View full text |Cite
|
Sign up to set email alerts
|

Urocortin 2 acts centrally to delay gastric emptying through sympathetic pathways while CRF and urocortin 1 inhibitory actions are vagal dependent in rats

Abstract: We characterized the influence of the selective corticotropin-releasing factor 2 (CRF(2)) receptor agonist human urocortin 2 (Ucn 2), injected intracisternally, on gastric emptying and its mechanism of action compared with intracisternal CRF or urocortin (Ucn 1) in conscious rats. The methylcellulose phenol red solution was gavaged 20 min after peptide injection, and gastric emptying was measured 20 min later. The intracisternal injection of Ucn 2 (0.1 and 1 microg) and Ucn 1 (1 microg) decreased gastric empty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
53
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 50 publications
4
53
0
Order By: Relevance
“…As such, h/rCRF has been used as the inhibitory control for comparison in this study. From the data obtained, it is evident that an ICV injection of h/rCRF (1 nmol) significantly delays gastric emptying of a solid nutrient meal, which is consistent with a previous report that used gastric emptying of a non-nutrient, semi-liquid meal through intracisternal administration (51). Although the half-life of h/rCRF is reportedly less than 10 min in human cerebrospinal fluid (52), the results from our current study show that the ICV h/rCRF injection (1 nmol) effectively inhibits the 2-h rate of gastric emptying of a solid nutrient meal in conscious, fasted rats.…”
Section: Discussionsupporting
confidence: 90%
“…As such, h/rCRF has been used as the inhibitory control for comparison in this study. From the data obtained, it is evident that an ICV injection of h/rCRF (1 nmol) significantly delays gastric emptying of a solid nutrient meal, which is consistent with a previous report that used gastric emptying of a non-nutrient, semi-liquid meal through intracisternal administration (51). Although the half-life of h/rCRF is reportedly less than 10 min in human cerebrospinal fluid (52), the results from our current study show that the ICV h/rCRF injection (1 nmol) effectively inhibits the 2-h rate of gastric emptying of a solid nutrient meal in conscious, fasted rats.…”
Section: Discussionsupporting
confidence: 90%
“…The urocortin 2 gene is abundantly expressed in the hypothalamic nuclei, including the PVN, which are involved in the regulation of feeding and gut motility. Previous studies have shown that urocortin 2 suppresses food intake and delays gastric emptying (16,18). In addition, stimulation of the CRF2 receptor with urocortin 2 induces anxiogenic responses in a wide variety of rodent anxiety models (19).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that Ucn2 and other members of CRF family peptides delay gastric emptying, and their expression is induced by lipopolysaccharide injection in rats (Czimmer et al 2006, Yuan et al 2012; Ucn2 inhibits the hypoxia-induced apoptosis in mesenteric arterial smooth muscle cells from spontaneously hypertensive rats (Tao et al 2006), and i.v. injection of Ucn2 increases plasma angiotensin II and noradrenaline concentrations, cardiac output, heart rate and left ventricular ejection fraction, and renin activity in healthy humans (Davis et al 2007).…”
Section: Discussionmentioning
confidence: 99%